Effects of total asset turnover, current ratio, and debt-to-equity ratio on the profit margin ratios - Kadhim Kamal Ahmad; Shakhawan Saeed Sangawi; Darun Tahir Ahmad (Privietlab, 2026)
This study aims to examine how the profit margin ratios of industrial sector companies listed on the Iraqi Stock Exchange between 2018 and 2023 are affected by the debt-to-equity ratio, current ratio, and total asset return. In this study, a quantitative methodology was used to analyze audited data of financial lists using EViews 12 software. It aims to show the effects of each of the dependent variables of net profit margin (NPM) and gross profit margin (GPM) on the independent variables of debt-to-equity ratio (DER), current ratio (CR), and total asset turnover (TAT). The results based on panel data from 10 manufacturing sector firms indicate the inter-variable effect as follows: The net profit margin (NPM) is significantly impacted negatively by DER, while GPM is positively impacted by DER. This NPM effect indicates that financial effects further reduce profitability. Nevertheless, CR has a slight beneficial impact on GPM and a non-significant negative impact on NPM. In addition, TAT indicates operational inefficiencies by increasing GPM and significantly reducing NPM. To promote sustainable growth in the Iraqi industrial sector, the report recommends increasing asset efficiency, optimizing capital structure, and strengthening liquidity management. This study makes several recommendations for legislators, investors, and corporate executives.